Language and Communication in Mathematics Education International Perspectives - Moschkovich, Judit N.; Wagner, David; Bose, Arindam; Rodrigues Mendes, Jackeline; Schütte, Marcus (ICME-13 Monographs, 2018)
VI, 279 p. 27 illus.